Recovery position significantly associated with a reduced admission rate of children with loss of consciousness. Issue 6 (25th January 2016) - Julliand, Sebastien; Desmarest, Marie; Gonzalez, Leticia; Ballestero, Yolanda; Martinez, Abel; Moretti, Raffaella; Rivas, Aristides; Lacroix, Laurence; Biver, Armand; Lejay, Emilie; Kanagarajah, Lakshmi; Portillo, Nancy; et al.
Abstract : Background: Loss of consciousness (LOC) is often seen in children. The response of caregivers to a child with LOC has been poorly investigated. Potential caregivers (parents, teachers) seem to have a poor knowledge of the recovery position (RP)—that is, the position into which an unconscious child should be placed in order to protect the airway. Objectives: To report the management and diagnoses of LOC in childhood, and to evaluate variables associated with an increased hospital admission rate. Methods: We conducted a prospective cohort study of consecutive children aged between 0 and 18 years diagnosed with LOC at 11 paediatric emergency departments (PEDs) of 6 European countries. The enrolment period was 3 months. Data were obtained from parental interviews, PED reports and clinical examination. Results: 553 children were enrolled. The most frequent final diagnoses causing LOC were seizures (n=278, 50.3%), and vasovagal syncope (n=124, 22.4%). Caregivers put the child in the RP in 145 cases (26.2%). The RP was independently associated with a significant decrease in the admission rate (aOR=0.28; 95% CI 0.17 to 0.48; p<0.0001). Conclusions: Our study demonstrates for the first time that the RP may reduce the admission rate of infants with LOC. Caregivers often perform inadequate manoeuvres when a child becomes unconscious. Campaigns aiming at increasing knowledge of the RP should be promoted.